Visual outcome after full refractive correction of anisometropic amblyopia among 5-15 years old children (Journal of National Institute of Ophthalmology, 2026)
Anisometropic amblyopia is the most common cause of visual morbidity in childhood which is characterized by reduced spatial vision due to refractive error. This study was planned to determine the visual outcome after full refractive correction of anisometropic amblyopia among 5-15 years old children. The Cross sectional interventional study was conducted conducted in the Departments of Community Ophthalmology and Ophthalmology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from March 2017 to august 2019. Children (5-15 years) having myopic, hypermetropic & astigmatic refractive error between two eyes will be minimum 1.0 D difference after refraction and didn’t get any treatment for this problem yet were the study population. Total 52 untreated children were included in the study. 3 children did not attend the follow up visit. The mean age of the subjects of our study was 9.47 years, range of age was 5-15 years. 44 (89.8%) patients were bilateral & 5 (10.2%) were unilateral. After full correction of refractive error with spectacles alone improved anisometropic amblyopic eyes visual acuity an average of 2.3 lines in snellen’s chart. Visual acuity improved from baseline by 2 or more lines (95% CI) in 85% of the patients and by 3 or more lines in 49.3%. This improvement is statistically significant (P